Effects of family history of diabetes on pancreatic β-cell function and diabetic ketoacidosis in newly diagnosed patients with type 2 diabetes: a cross-sectional study in China. Issue 1 (11th January 2021) - Xiong, Xiaofen; Wei, Ling; Xiao, Ying; Han, Yachun; Yang, Jinfei; Zhao, Hao; Yang, Ming; Sun, Lin
Abstract : Objective: To investigate the association between a parental and/or sibling history of diabetes and clinical characteristics. Design: A cross-sectional study. Setting: The data were collected from the endocrinology department of The Second Xiangya Hospital of Central South University from June 2017 to October 2019. Participants: A total of 894 newly diagnosed patients with type 2 diabetes were recruited. Data on clinical characteristics were collected from patient medical records. Pancreatic β-cell function and insulin resistance were calculated with the homeostatic model assessment. SPSS V.25.0 was used to perform the analysis. Results: The percentages of patients with parental and sibling histories of diabetes were 14.8% and 9.8%, respectively. The prevalence of diabetic ketoacidosis (DKA) was 3.9%. Compared with those with no parental history of diabetes, patients with a parental history of diabetes were characterised by early-onset disease (41.70±10.88 vs 51.17±14.09 years), poor glycaemic control of fasting blood glucose (10.84±5.21 vs 8.91±4.38 mmol/L) and a high prevalence of DKA (7.6% vs 3.3%). The patients with a sibling history of diabetes had later disease onset (56.05±9.86 vs 49.09±14.29 years) and lower BMI (24.49±3.48 vs 25.69±3.86 kg/m 2 ) than those with no sibling history of diabetes. Univariate regression suggested that both parental history (p=0.037) and sibling history (p=0.011) of diabetes were associated with β-cell function; however, multiple regression analysis showed that only a sibling history of diabetes was associated with β-cell function (p=0.038). Univariate regression revealed a positive correlation between parental history of diabetes (p=0.023, OR=2.416, 95% CI 1.132 to 5.156) and DKA. Unfortunately, this correlation was not statistically significant for either patients with a parental history (p=0.234, OR=1.646, 95% CI 0.724 to 3.743) or those with a sibling history (p=0.104, OR=2.319, 95% CI 0.841 to 6.389) after adjustments for confounders. Conclusion: A sibling history of diabetes was associated with poor β-cell function, and a parental history of diabetes was associated with poor glycaemic control and a high prevalence of DKA.